Potential Of Tamarind Turmeric Instant Herbal Drink As A Student Entrepreneurship Project - Soegiantoro, Didiek Hardiyanto; Widhiarso, Ari; Sepiany, Sepiany; Nazna, Christy; Rezeki, Leani Sri; Farasi, Priska Ica Sari (Sean Institute, 2024)
The article discusses the potential of tamarind turmeric instant herbal products as part of an entrepreneurship project for pharmacy students. It emphasizes the importance of combining pharmaceutical knowledge with entrepreneurial skills, which can lead to innovation in the healthcare industry. The project involves minimal investment in equipment for powdering ingredients and offers a convenient product for consumers through instant drink mixes. Leveraging e-commerce and digital marketing strategies, students can promote their product effectively. Collaborations with health influencers and participation in local health fairs can enhance product visibility and consumer feedback. The primary aim of the research is to conduct an organoleptic evaluation of the tamarind turmeric instant herbal products and assess sales performance. A descriptive qualitative research design was adopted to gather sensory evaluations and consumer feedback. The results indicate that these herbal products are becoming popular due to their health benefits, including antioxidant and anti-inflammatory properties. The organoleptic attributes were evaluated, focusing on factors such as color, aroma, taste, and texture. The findings showed that the product has a yellowish-brown color, a tangy and citrusy aroma with earthy undertones, a tangy and slightly sour taste with mild spiciness, and a smooth texture that dissolves easily in water. The visual appeal of the product plays a significant role in consumer preference, as color can indicate the presence of beneficial ingredients like curcuminoids in turmeric. The sales performance of instant turmeric and tamarind drinks shows consumer acceptance in hedonic tests on taste, color, and aroma with the results of like and very-like.